Soil Biochemical Property Response to Drought Effects under Land-Use Change in the Context of Climate Change - Bùi, Hạnh Mai (2020)
The study has identified that droughts in coastal plains occurred more frequently and more severely than mountainous areas. In the period of 2003 – 2019, the drought situation in Quang Nam became more complicated. While the drought frequency has tended to increase, the drought intensity has tended to decrease. Moreover, drought is also one of the reasons of land-use change in Quang Nam. Although the agricultural land area increased slightly (0.83%), the forest land area also increased significantly by 5.86%. This change is aimed to adapt to unpredictable drought situations. The current study attempts to identify differences in soil biochemical factors, which are influenced by drought and land-use change. The results illustrated a number of interesting trends, which suggest that under the impact of drought and land-use change in Quang Nam in the period of 2003 – 2018, not only do the soil chemical properties change but also drought reduced the activity of soil microorganisms. This was reflected in the experiments, which identify soil respiration and microbial biomass in the low WHC and the land-use change. The low value of C:N ratio in forest soil and pineapple soil indicated a high rate potential of SOM decomposition. However, when drought occurred, the MBC and soil respiration of both land-use types decrease significantly compared with soil at appropriate soil moisture. By contrast, the MBN values of both land-use types under the impact of drought increased. The reason might be that fungi are the dominant microorganism in the microbial community in two soil types. When water shortages occurred, fungi could contribute to the maintenance of C and N cycling (Treseder et al., 2018). Moreover, the conversion of land-use has caused soil pH, C:N ratios and MBN to change. Pineapple cultivation has caused those soil indices to decrease.